2018
DOI: 10.3390/rs10081218
|View full text |Cite
|
Sign up to set email alerts
|

Individual Tree Crown Segmentation and Classification of 13 Tree Species Using Airborne Hyperspectral Data

Abstract: Knowledge of the distribution of tree species within a forest is key for multiple economic and ecological applications. This information is traditionally acquired through time-consuming and thereby expensive field work. Our study evaluates the suitability of a visible to near-infrared (VNIR) hyperspectral dataset with a spatial resolution of 0.4 m for the classification of 13 tree species (8 broadleaf, 5 coniferous) on an individual tree crown level in the UNESCO Biosphere Reserve ‘Wienerwald’, a temperate Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 76 publications
4
108
0
1
Order By: Relevance
“…We found that the use of vegetation indices improved the classification performance compared to the sole use of spectral signatures. Similar results were reported by Puletti et al [28] and Maschler et al [12]. The most relevant vegetation indices were based on the same bands, which show high importance in the models based only on spectral bands.…”
Section: Sentinel-2 Bands and Vegetation Indicessupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the use of vegetation indices improved the classification performance compared to the sole use of spectral signatures. Similar results were reported by Puletti et al [28] and Maschler et al [12]. The most relevant vegetation indices were based on the same bands, which show high importance in the models based only on spectral bands.…”
Section: Sentinel-2 Bands and Vegetation Indicessupporting
confidence: 90%
“…As a result, data with higher spatial, spectral and temporal resolutions are available. Analysis of hyperspectral data demonstrated the added value of the dense spectral sampling for the separation of tree species [10][11][12][13]. Multi-spectral, very high resolution (VHR) satellite data were successfully used for mapping tree species distribution for up to ten different species [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral features for tree species classification are relatively common (e.g. Maschler et al, 2018), but few papers have focused on integrating hyperspectral data into tree detection alongside other sensors. Hyperspectral data is available for all NEON sites, and we utilized a three-band composite image to assist in annotating the Eastern Deciduous site (Figure 9), illustrating the usefulness of hyperspectral data to distinguish adjacent tree crowns with human vision.…”
Section: Discussionmentioning
confidence: 99%
“…Maschler et al [36] applied mean shift to airborne hyperspectral image twice: Firstly to differentiate short and tall stands, and secondly to segment individual tree crowns, to classify a temperate forest.…”
Section: Related Workmentioning
confidence: 99%